Uncovering the antifungal potential of Cannabidiol and Cannabidivarin - Dinh, Hue; Fernandes, Kenya E.; Erpf, Paige E.; Clay, Evie J. M.; Tay, Aidan P.; Nagy, Stephanie S.; Schaefer, Sebastian; Maharjan, Ram; Lenardon, Megan D.; Multari, Dylan H.; Haynes, Paul A.; Paulsen, Ian T.; et al. (PLOS Neglected Tropical Diseases, 2025)
Author summary Fungal infections are a major public health issue affecting over a billion people globally. Current antifungal treatments are increasingly compromised by drug resistance and show adverse side effects, underscoring the urgent need for novel therapies. Phytocannabinoids like Cannabidiol (CBD) and Cannabidivarin (CBDV), which have established safety profiles and are approved or under investigation for neurological conditions, may hold promise in this domain. Despite this, their antifungal properties remain underexplored. Here we show that CBD and CBDV exhibit in vitro antifungal activity against various fungi, including common dermatophytes causing “jock itch” and “athlete’s foot”, as well as WHO Critical Priority pathogens, such as Cryptococcus neoformans. Further investigation in C. neoformans revealed that CBD and CBDV appear to work by disrupting biofilms, altering fungal cell morphology, and impacting metabolic pathways and membrane integrity, as observed through comparative proteomics. Further, in vivo experiments using Galleria mellonella infected with C. neoformans revealed significantly improved survival with CBD treatment. The in vitro and in vivo antifungal efficacy of CBD and CBDV established in this study highlights the potential of phytocannabinoids to address the pressing need for effective and new treatments for fungal infections.